2018
DOI: 10.1111/cch.12547
|View full text |Cite
|
Sign up to set email alerts
|

Comparing impact on the family and insurance coverage in children with cerebral palsy and children with another special healthcare need

Abstract: There is limited evidence highlighting differences between the impact of caring for a child with CP and caring for other CSHCN. Caring for a child with CP has a significant impact on the family, despite insurance coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Cerebral palsy is characterized by movement and posture abnormalities accompanied by secondary complications such as joint contracture and postural deformity [13] and requires various treatments over an extended period of time. A higher occurrence of unmet health care needs among children with special health care needs including CP has been identified in various studies [7][8][9][10][11]. We thought that understanding the state of care provided to children with CP would be the basis for solving unmet health care needs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cerebral palsy is characterized by movement and posture abnormalities accompanied by secondary complications such as joint contracture and postural deformity [13] and requires various treatments over an extended period of time. A higher occurrence of unmet health care needs among children with special health care needs including CP has been identified in various studies [7][8][9][10][11]. We thought that understanding the state of care provided to children with CP would be the basis for solving unmet health care needs.…”
Section: Discussionmentioning
confidence: 95%
“…A higher occurrence of unmet health care needs among children with special health care needs has been identified in various studies. Using the 2007 National Survey of Children's Health, the authors found that about 4% of US children have unmet medical care needs [7,8]. McManus et al reported that children who need special health care needs have an unmet rehabilitation need and there was a difference in the therapeutic use according to severity of developmental condition [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, a child' s health care cost may exacerbate a family' s financial strain and hinder caregiver employment opportunities, a key driver toward housing insecurity. [30][31][32][33] This was a single-state observational study in which we evaluated only select Medicaid plans within a CM population, which limits its generalizability. However, we were able to examine health plan rather than singleinstitution usage data.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 studies covered by the 30 included articles, 9 were conducted in the United States, [17][18][19][20][21][22][23][24][25] with a tenth cross-national…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…46 All included studies were observational, but used various data collection modes and recall periods. Sixteen used a cross-sectional study design, [18][19][20][21][22][25][26][27][28][29][30]36,39,42,43,46 collecting data with paperpencil questionnaires or phone-administered surveys [18][19][20][21][22]25,[27][28][29]36,39,42,43,46 or combining face-to-face interviews with a self-report questionnaire. 26,30 Of these 16, 7 studies assessed expenses retrospectively, with a recall period of 12 months.…”
Section: Out-of-pocket Medical Expenses Out-of-pocket Nonmedical Expensesmentioning
confidence: 99%